The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1590/s0037-86822006000400008
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and kinetics of natural killer cell cytotoxicity in human malaria as evaluated by a novel stepwise cytotoxicity assay

Abstract: Malaria causes important functional alterations of the immune system, but several of them are poorly defined. To evaluate thoroughly the natural killer cell cytotoxicity in patients with malaria, we developed a technique capable to assess both the dynamics and the kinetics of the process. For the kinetics assay, human peripheral blood mononuclear cells were previously incubated with K562 cells and kept in agarose medium, while for the dynamics assay both cells were maintained in suspension. NK activity from pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…The increased of the NK population proportions during acute and, probably, during severe malaria described in this study, in addition to a positive correlation between NK cytotoxicity and levels of parasitaemia reported by other authors in patients infected with P. falciparum [32], confirms the induction of robust cellular responses to P. falciparum in naturally infected individuals form the American continent, and highlights the importance of further exploring the role of these cells and theirs subsets in the immunopathology during severe malaria outside Africa.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The increased of the NK population proportions during acute and, probably, during severe malaria described in this study, in addition to a positive correlation between NK cytotoxicity and levels of parasitaemia reported by other authors in patients infected with P. falciparum [32], confirms the induction of robust cellular responses to P. falciparum in naturally infected individuals form the American continent, and highlights the importance of further exploring the role of these cells and theirs subsets in the immunopathology during severe malaria outside Africa.…”
Section: Discussionsupporting
confidence: 82%
“…Studies on the dynamics of NK activity in malaria patients revealed heterogeneous results, particularly in P. falciparum infected individuals. Nevertheless, confirmation of NK activation has been observed in subjects with Plasmodium vivax or P. falciparum infection [32]. …”
Section: Discussionmentioning
confidence: 99%
“…There is little data in the literature related to a decline in NK cells activity in uncomplicated malaria. However, Ribero-Dias and coll [14] denounced an alteration of the cytotoxic function of NK cells during Plasmodium falciparum malaria. In another context of a murine model, Dogruman and coll [15] reported lower expression of NK markers in P. berghei infected mice than in healthy witnesses.…”
Section: Discussionmentioning
confidence: 99%